EFEKTIVITAS LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK POSITIVE REINFORCEMENT DALAM MENINGKATKAN DISIPLIN SISWA KELAS VIII DI SEKOLAH MENENGAH PERTAMA SULTAN AGUNG KASIYAN TIMUR PUGER - Masrukhin, Akhmad Rudi; Uke, Ora Gorez; Fitri Kamala, Rofiqoh (Universitas Al-Falah As-Sunniyah Kencong Jember, 2023)
Discipline is an attitude or behavior that must be applied by students to support the success of the educational process itself. It is very important to improve disciplined behavior. With techniques to increase discipline, namely techniques (Positive Reinforcement) to be oriented towards changing behavior in students The general main problem in this research is: Are group guidance services using positive reinforcement techniques effective in increasing student discipline? Meanwhile, the sub-main problems in this research are: (1) Are group guidance services using positive reinforcement techniques effective in increasing student discipline in obedience in using school attributes in class VIII of Sultan Agung Kasiyan East Middle School for the 2022-2023 academic year? (2) Are group guidance services using positive reinforcement techniques effective in increasing student discipline in obeying and punctually starting school hours in class VIII of Sultan Agung Kasiyan Timur Middle School for the 2022-2023 school year? (3). Are group guidance services using positive reinforcement techniques effective in increasing obedience and accuracy in carrying out school rules in class VIII of Sultan Agung Kasiyan East Middle School for the 2022-2023 school year? The general objective of the research is to determine the effectiveness of group guidance services using positive reinforcement techniques in improving student discipline at Sultan Agung Kasiyan Timur Middle School for the 2022-2023 academic year.This research uses a quantitative approach, field research type and One Group Pretest Posttest Design. The sample technique in this research was a purposive sampling technique with a sample size of 11 students. Data collection includes: Questionnaires, interviews, observation and documentation. The data analysis technique in this research is the paired sample t-test using SPSS version 25